A Phenomenological Study on Teachers’ Implementation of Think-Aloud Scaffolding Technique in Grade 4 Mathematics - Gemcer Selda (Research Synergy Foundation, 2025)
This study explored the experiences of Grade Four mathematics teachers in implementing the Think-Aloud Scaffolding Technique (TAST), particularly in classrooms with Indigenous Peoples (IPs) students in the Bongabong District. Anchored on a phenomenological approach, the research examined how TAST influenced teaching strategies, student engagement, and mathematical comprehension. Semi-structured interviews with eight teachers were conducted, and data were thematically analyzed to identify recurring patterns and insights. Results revealed that TAST strengthened students’ problem-solving and critical thinking skills through verbalized modeling and step-by-step reasoning. Teachers found the technique effective in bridging learning gaps and promoting inclusive participation among IP learners. However, challenges such as language differences and varying learning paces were noted. The findings highlight the importance of culturally responsive pedagogy, personalized scaffolding, and the integration of visual and contextual supports. Educationally, this study underscores how TAST can be adapted and scaled for broader STEM contexts to enhance inclusivity and comprehension. It provides valuable implications for teacher professional development, curriculum refinement, and policy-making aimed at improving mathematics instruction across diverse learning environments.